Study The Severe Effects of Iron Compounds Presenting in Sandstone on the Deterioration of Wall Paintings of Archaeological Tombs in Bahariya Oasis - Egypt - Kader, Rabea Radi Abdel; El–Sayed, Shaimaa Sayed Mohamed; Abo-El Yamin, Ahmed (Budapest International Research and Critics University, 2019)
The Wall paintings in Bahariya oasis expose to various deterioration factors, especially the resulted deterioration from the geological nature of sandstones' supports; sandstone of Bahariya formation is considered the weakest sandstone type in Egypt because of its geological formation which contains a very big percentage of iron oxides. Sandstone samples were taken, analyzed and examined by x-ray diffraction and scanning electron microscope, the iron oxides are thecement material in sandstone which affect negatively on the wall paintings in the selected tombs (Badi –Ishtarand Bannantiu tombs),they caused a lot of deterioration phenomena to the wall painting layers like: layers loss,black spots, cracking through all the layers and sandstone support weakness that threatens the remaining wall paintings and the safety of the tombs. Iron oxides percentage in Badi – Ishtartomb is more than Bannantiu tomb and this is reflected on the wall paintings case in Badi – Eshtar. This research sheds the light on this phenomenon and its effect on the wall painting's deterioration.